Leveraging Tuan Guru's Standing Role: A Dramaturgical Approach to Stunting Prevention in East Lombok, Indonesia - Harian, Paenal Juni; Qalbiy, Shafwatu; Wahidah, Ananda; Yuliana, Devi; Nabani, Taqiyudin (Ilomata International Journal of Social Science, 2024)
Stunting is a national health problem in toddlers that is currently a significant concern for the government. Stunting cases are still a problem that needs to be resolved and is increasing. This research aims to determine the actual conditions of stunting in East Lombok and the central role of the tuan guru figure in efforts to accelerate the handling of stunting in East Lombok. The method used is qualitative with a phenomenological approach with 40 informants from 4 categories. The research results show that East Lombok Regency is the area with the most toddlers suffering from stunting in NTB based on February 2024 data, with Sikur District being a red zone with a prevalence of 30.33%. Prevention and handling of stunting are still carried out conventionally by relying on socialization and integrated health posts from health centers. The presence of the tuan guru figure amid community life who is a role model and role model for the community in everyday life is an alternative solution that can accelerate the reduction in stunting rates and maximize prevention efforts. Dramaturgical actions in front and behind the stage by the tuan guru can be an alternative solution to expedite the handling of stunting in East Lombok through preaching packaged concerning the general conditions of the target community. Parenting pattern intervention is the main target of Tuan Guru's preaching in terms of preventing and handling stunting to create healthy and prosperous families.